Systematic Review: Seventy-Seven Cases of Signet Ring Cell Adenocarcinoma of the Bladder - Kenneth Keen Yip Chew; Madison Boot; Katelyn Wilson; Cameron Sowter; Wei Xuan; Raymond Stanton; Paul Bergamin (Société Internationale d’Urologie Journal, 2024)
Background: Signet ring cell adenocarcinoma (SRCC) of the bladder is a rare and aggressive histological subtype of bladder cancer. Due to its infrequency, the understanding of its clinical behaviour, treatment strategies, and outcomes remains limited, being primarily derived from isolated case reports and series. Objective: To systematically review and analyse the available literature on SRCC of the bladder, emphasizing its clinical characteristics, diagnostic approaches, treatment modalities, and outcomes. Material and Methods: A comprehensive search was conducted across PubMed, Embase, and Medline following the PRISMA guidelines, including case reports, case series, observational studies, and clinical trials reporting on bladder SRCC. Results: We included 38 articles reporting on 77 patients, primarily males (79.2%), with a median age of 64 years. The most common presenting symptoms were haematuria (64.8%) and lower urinary tract symptoms (46.3%). All the diagnoses were based on histopathological examination of bladder tissue samples and immunohistochemistry. Mixed histological types of bladder cancer were found in 20.7% of cases, most commonly urothelial carcinoma (61.1%). The treatments varied, with 53.2% of patients undergoing radical cystectomy, 24.7% receiving radiotherapy, and 16.9% receiving chemotherapy. The five-year survival rates were 9.4%. Conclusion: Bladder SRCC presents aggressively, with varied treatment strategies; however, radical cystectomy appears to be the optimal means of surgical management for organ-confined disease. The overall survival rate is low, highlighting the need for further research to understand and manage this rare bladder cancer variant. All patients should undergo evaluation to exclude extravesical primaries. This systematic review contributes to a better understanding of this disease and may guide clinical management strategies.